Mini Review: Transport of Hydrophobic Polymers Into the Plant Apoplast - Xin, Anzhou; Herburger, Klaus (Frontiers in Plant Science, 2021)
The plant apoplast contains the four hydrophobic polymers lignin, suberin, cutin, and cutan, which are crucial for stress resistance, controlling solute diffusion and strengthening the cell wall. Some of these polymers are widely used in industry and daily life products such as all wood-containing goods (lignin) and wine cork (suberin). Despite the importance of these polymers, several aspects of their formation remain unknown. This mini review highlights technical bottlenecks in the current research and summarizes recent insights into the precursor transmembrane transport, an essential step in the polymer formation. We also briefly discuss how some of the remaining knowledge gaps can be closed and how a better understanding of these biopolymers will benefit other research fields.